Odpowiedź:
Szczegółowe wyjaśnienie:
3x
(a+a^2)/2
16%k=0,16k
_____________
1,5x^2y∙(-2)∙x∙y^2= -3x^3y^3
______________
a) 6a – 4 + 3a – 3 - 5a + 10= 4a+3
dla a= - 6
4*(-6)+3= -24+3= -21
b) 3x + 4y + 10 - 4x + 3y =7y-x+10
dla x= 4, y= -0,3
7*(-0,3) -4+10= -2,1 -4+10= -6,1+10= 3,9
c) 5(x^2 – x + 3) – 0,5(16x^2 - 10x + 12) =5x^2-5x+15 -8x^2+5x-6= -3x^2+9
dla x = -9
-3*(-9)^2+9=-3*81 +9= - 243+9=-234
d) x(4xy + 3y) – y(5x2 + 3x - 2y) =4x^2y+3xy-5x^2y-3xy+2y^2= -x^2y+2y^2
dla x = - 0,5, y = 10
-(-0,5)^2*10 +2*10^2=-0,25*10+2*100= -2,5+200=197,5